Pulmón en Herradura - Romero Rojas, Nery (2025)
Horseshoe lung is a rare congenital pulmonary malformation in which the postero basal regions of the right and left lungs are fused by a pulmonary band or isthmus, it is frequently associated with unilateral pulmonary hypoplasia, cardiac dextroposition and anomalous pulmonary venous drainage; its prevalence is unknown. We present the case of a male fetus with a horseshoe lung, weighing 200 g, associated with anencephaly, cervical rachischisis, agenesis left kidney, anterior rotation right kidney and single umbilical artery. The mother was a 17-year-old secundary mother, with no prenatal care or significant medical history.